Sentiment Analysis of the Role and Connotation of Office Secretary through Twitter - Rouna Paoki; Jimmy H Moedjahedy (Universitas Negeri Surabaya, 2023)
A secretary is responsible for coordinating and attending board and committee meetings, producing minutes, acting as a liaison between directors, officers, and shareholders, and directing activities related to the annual shareholders' meeting. The presence of sexual harassment or an intimate relationship with a married supervisor is one of the challenges a woman encounters at work. Consequently, the secretary role and the term secretary are frequently used negatively. This research seeks to do a Twitter-based sentiment analysis of the secretary's words and position. Using the Tweppy API, the sentiment analysis method was applied to the research by analyzing phrases on Twitter. This investigation makes use of five keyword instances. There are 31.73 percent favorable answers to scenarios involving the words